TELE-TOOLS IN COMMUNITY REHABILITATION - REACHING THE UNREACHED - Amit Ranjan; Javed Ahmed; Ravi Gaur (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Community rehabilitation aims to improve the quality of life of persons with disabilities and their families by providing accessible and affordable rehabilitation services within their local surroundings. Despite this, the efficacy and accessibility of community rehabilitation services in India are hindered by several obstacles, including sociocultural factors, lack of trained personnel, and geographical distance. Tele-tools, which refer to the utilization of information and communication technologies (ICTs) for the provision and assistance of community rehabilitation services, present a promising alternative to address these obstacles and amplify the scope and effectiveness of community rehabilitation. This essay examines the several facets of tele-tools in community rehabilitation and offers suggestions for future study and implementation.